Избранные романы: В спец. ред. Ридерз Дайджест - Л. Чайлд (Ридерз Дайджест, 2002)
Экземпляры: (20130408) / Инвентарный номер: 48233 / Цена: 80.00 / Сис.шифр: И(Англ) 48233 / Авт.знак: И 32 / ГРНТИ: 17.82.30 / ББК: 84(4Вел)